PENGARUH AUDIT TENURE, AUDITOR SWITCHING, AUDIT FIRM SIZE TERHADAP AUDIT QUALITY - Zefanya Immanuel; Hendro Lukman (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims to obtain empirical evidence about the effect of Audit Tenure, Auditor Switching, Audit Firm Size, and Auditor’s Fee Towards Audit Quality. This research uses secondary data obtained from the site www.idx.co.id. The population of this research is all of manufacture company in consumer’s good section listed in the Indonesia Stock Exchange (IDX) during the year 2017-2019. This research is conducted with a sample of 101 data. Furthermore, data collection techniques used in this research is secondary data that is processed using Statistical Package for the Social Sciences (SPSS) ver 21.0 software. The statistical method used to test the hypothesis is the multiple linear regression method. The results of this research show that all variables on this research has no significant effect on Audit Quality and also Litigation Risk has weakened moderated on Auditor’s Fee towards Audit Quality.